Kalman Filtering Algorithm for Electric Power Quality Analysis: Harmonics and Voltage Sags Problems - Mostafa, M.A. (2007 Large Engineering Systems Conference on Electric Power Engineering, 2007)
Power quality involves how close the voltage waveform is to being a perfect sinusoid with a constant frequency and amplitude. In this paper, we review the applications of linear Kalman filtering algorithm on-line for electric power quality analysis. These applications include the measurement of harmonics and voltage sags. Mathematical models for each problem are developed to suite the filter and tested using simulated examples. Conclusions are drawn at the end of the text.